Israel as a Mixed Jurisdiction - Rivlin, Eliezer (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
Like in most Western countries, the legal system in Israel is constantly evolving. Israel is a mixed jurisdiction in many respects. Historically, during the time of the Ottoman Empire, the land of Israel was ruled by Turkish law, which was followed by British law during the time of the British Mandate. Today, Israel’s legal system still reflects a mixture of civil law and common law. This mixture is evident, for example, in the combination of codified law and precedent-based law. Several areas of the law were codified, at the time of the British Mandate, in ordinances that remain binding today. However, these ordinances were supplemented and widely interpreted in Israel’s case law, and an “Israeli common law” was created. Today, legislative efforts are being made to codify this new common law.The mixed nature of substantive law in Israel is also illustrated by Israel's constitutional regime. While Israel has no formal constitution, it has a partial bill of rights (the basic laws) enacted by its parliament. In 1995, the Israeli Supreme Court decided, referring to American constitutional law, that it had the authority to invalidate “unconstitutional laws”. In its decision, the Supreme Court relied on a limitation clause, included in the new basic laws and inspired by the Canadian Charter of Rights and Freedoms. Since then, the Israeli Supreme Court has developed a number of constitutional rights from these basic laws, influenced by both the American concept of liberty and the European concept of human dignity.Finally, comparative law plays an important role in Israeli case law. While British common law no longer binds the Israeli judiciary, judges have wide discretion to use comparative law in their decisions. When relevant, referring to foreign law may be of great assistance to a judge by providing inspiration in a difficult case. Utilizing many different sources of law may help to create harmony between various jurisdictions, especially in times of increasing globalization.